Inside-out, outside-in, or all-in-one? The role of network sequencing in the elaboration of ideas - ter,Wal A; Criscuolo,P; Salter,A (Academy of Management Journal, 2023)
The structure of advice and support networks within organizations has a profound impact on the elaboration of novel ideas. We explore how the sequence in which individuals expose ideas to their network contacts affects their innovation performance. We argue that, during idea elaboration, inside-out network sequencing – that is, mobilizing input and support from inner-circle ties before outer-circle ones – yields an innovation performance advantage over outside-in network sequencing and all-in-one mobilization of network contacts. Inside-out network sequencing generates valuable early feedback and support from inner-circle ties that actively engage with ill-defined, ill-structured and uncertain ideas, and delays exposure to outer-circle ties until ideas can better withstand criticism from beyond the social circle where they emerged. We further contend that the benefits of inside-out network sequencing are amplified in environments that lack support for innovation. Using an analysis of survey data and archival innovation performance records for 301 R&D scientists and engineers in a large multinational firm, we find support for our predictions.